Preparation method and application of defect ordered hexagonal hole structure oxidation-resistant MXene material

Through the process of molten salt coating etching under high-temperature air atmosphere and rapid cooling after high-temperature sintering at 1600°C, MXene material with regular hexagonal holes was prepared, and a micro-oxidation protective layer was formed on its surface, solving the problem that MXene material is easily attacked by oxygen molecules and water molecules in neutral water electrolytes, and significantly improving its antioxidant performance and cycle stability.

CN119612515AActive Publication Date: 2025-03-14LIAONING UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202411127638.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2025-03-14
Estimated Expiration
2044-08-16

AI Technical Summary

Technical Problem

The existing MXene materials are easily attacked by oxygen molecules and water molecules in the electrolyte of neutral water system, resulting in structural damage, which leads to a sharp drop in specific surface area and a sharp decline in specific capacity, affecting its long cycle stability.

Method used

Through molten salt coating method under high-temperature air atmosphere, combined with a short-term rapid cooling process after high-temperature sintering of 1600°C, a MAX phase Ti3AlC2 precursor with regular hexagonal holes was prepared, and a micro-oxidation protective layer was formed on its surface to reduce the aggressiveness of oxygen molecules and water molecules.

Benefits of technology

It significantly improves the oxidation resistance of MXene material, avoids a sharp drop in specific surface area and specific capacity, improves the rate performance and cycling stability of the material, and enables it to operate stably for a long time in a symmetrical supercapacitor of water system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612515A_ABST
    Figure CN119612515A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of an oxidation-resistant MXene material with a defect ordered hexagonal hole structure, and the preparation method comprises the following steps: mixing MAX phase Ti3AlC2 with hexagonal holes, CuCl2 and NaCl, loading into an alumina corundum square, covering with a NaCl salt bed boat, putting into a muffle furnace, and carrying out constant-temperature sintering at 820 DEG C in an air atmosphere for 3 hours; the method has the advantages that the process is simple and reasonable, a barrier for resisting attacks of oxygen molecules and water molecules is effectively constructed under the combined action of trace metal oxides on the surface of the MXene material, and the oxidation resistance of the MXene material is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a preparation method and application of a defect-ordered hexagonal pore structure antioxidant MXene material. Background Art

[0002] MXene materials are predicted to be a new generation of new energy storage materials and an ideal alternative to carbon electrodes due to their two-dimensional structure similar to carbon materials, controllable layer structure, high specific surface area, rich controllable surface functional groups, excellent conductivity and good chemical stability.

[0003] At present, the common etching method for MXene materials is a more severe hydrofluoric acid etching method, which takes a long time to etch and has certain hazards to the environment and human body. CN117945402A discloses "a method for preparing a multilayer hexagonal pore MXene material with carbon vacancy defects for aqueous potassium ion supercapacitors". This method puts dehydrogenated titanium powder, pure aluminum powder and modified spherical graphite powder into a vacuum hot pressing sintering furnace, and hot presses and sinters them in a vacuum hot pressing sintering furnace with argon as the protective atmosphere, and then cools them with liquid nitrogen to obtain a hexagonal carbon vacancy MAX phase Ti 3 AlC 2 ; Hexagonal pore MXene is prepared by microwave-assisted etching to obtain a multilayer hexagonal pore MXene negative electrode material. The advantage is that this method adopts a liquid-phase microwave-assisted etching method, which promotes the stratification of MXene materials and improves the energy density of Mene in electrochemistry. However, this method is a liquid-phase etching environment, and the surface of the obtained MXene material is hydrophilic hydroxyl and oxygen functional groups. The MXene material is easily attacked by oxygen molecules and water molecules in a neutral aqueous electrolyte, and oxidation occurs, which leads to structural destruction, causing a sharp drop in the specific surface area of ​​the MXene material, which in turn leads to a sharp attenuation of the specific capacity and a significant reduction in the rate performance, which seriously affects its long-cycle stability. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a defect-ordered hexagonal pore structure antioxidant MXene material with strong antioxidant properties and small mass specific capacity decay over a long period of charge and discharge, and its application.

[0005] The technical solution of the present invention is:

[0006] A method for preparing a defect-ordered hexagonal pore structure antioxidant MXene material, the specific steps of which are as follows:

[0007] (1) MAX phase Ti of hexagonal pores 3 AlC 2 Preparation

[0008] Dehydrogenated titanium powder, pure aluminum powder and modified spherical graphite powder were hot pressed and sintered for 4 h in an argon atmosphere, wherein the sintering temperature was 1600 ° C and the pressure head pressure of the vacuum hot pressing sintering furnace was set to 20 T; after the hot pressing sintering was completed, liquid nitrogen was extremely rapidly cooled for 0.5 h to obtain MAX phase Ti with hexagonal pores. 3 AlC 2 ;

[0009] (2) Preparation of multilayer hexagonal MXene by molten salt coating in high temperature air atmosphere

[0010] The MAX phase of the hexagonal hole is Ti 3 AlC 2 With CuCl 2 Mix with NaCl in a molar ratio of 1:3:6 and grind for 30 min to obtain the MAX phase Ti with hexagonal pores. 3 AlC 2 -CuCl 2 -NaCl mixed powder; a layer of NaCl salt bed is laid on the bottom of the alumina corundum boat, and then the hexagonal pore MAX phase Ti 3 AlC 2 -CuCl 2 -NaCl mixed powder was placed in an alumina corundum boat with a NaCl salt bed, and then the MAX phase Ti in the hexagonal pores 3 AlC 2 -CuCl 2 -NaCl mixed powder is covered with a layer of NaCl salt bed, and the Ark is placed in a muffle furnace and sintered at a constant temperature of 820℃ for 3h in an air atmosphere; since the NaCl salt bed in an air atmosphere cannot completely isolate oxygen, a small amount of Al can be generated during the sintering process. 2 O 3 The sintered product was naturally cooled to room temperature, and deionized water was added to dissolve and wash, the NaCl molten salt was removed, and the solid phase was retained; then, the CuCl 2 With FeCl 3 FeCl was added at a molar ratio of 3:4 3 The solution was filtered and washed with clean water, and the solid phase was retained to remove the copper element generated during sintering. 3 HCl solution was added in a molar ratio of 1:1 to remove metal impurities, and the solid phase was retained by filtration; the solid phase was retained after filtration; finally, deionized water was added for washing and the material was placed in an ultrasonic device for 1 hour to further remove impurity salts, and then filtered, vacuum dried and ground to obtain a defect-ordered hexagonal pore structure antioxidant MXene material (Defect-Ti 3 C 2 )

[0011] Furthermore, the molar ratio of the dehydrogenated titanium powder, the pure aluminum powder and the modified spherical graphite powder is 2.95:1.05:1.6.

[0012] Furthermore, the FeCl 3 The solution concentration is 1 mol / L.

[0013] Furthermore, the concentration of the HCl solution is 1 mol / L.

[0014] Furthermore, during hot pressing sintering, the sintering power is 50KW.

[0015] Furthermore, the diameter of the effective contact surface of the pressure head of the vacuum hot pressing sintering furnace is Φ90 mm.

[0016] Furthermore, the filling pressure of the argon protective atmosphere is 0.03 MPa.

[0017] An application of the defect-ordered hexagonal pore structure antioxidant MXene material prepared by the above-mentioned preparation method in aqueous potassium ion symmetric supercapacitors.

[0018] Furthermore, the defect-ordered hexagonal pore structure antioxidant MXene material is used as an electrode material for an aqueous potassium ion symmetric supercapacitor; the preparation process of the aqueous potassium ion supercapacitor is as follows:

[0019] (1) Preparation of defective multilayer hexagonal pore MXene electrodes

[0020] The defect-ordered hexagonal pore structure antioxidant MXene material was mixed with acetylene black and PVDF in a mass ratio of 8:1:1 and ground for 1 hour, NMP was added dropwise to form a slurry, coated on an aluminum foil current collector, and rolled flat, dried at 60°C for 24 hours, and maintained at a pressure of 20MPa for 30 seconds using a press to obtain a defect-ordered hexagonal pore structure antioxidant MXene material electrode;

[0021] (2) Assembly of aqueous potassium ion symmetric supercapacitors

[0022] The defect-ordered hexagonal pore structure antioxidant MXene material electrode as the negative electrode, the separator, and the defect-ordered hexagonal pore structure antioxidant MXene material electrode as the positive electrode are sequentially loaded into the capacitor shell, packaged, and injected with electrolyte to obtain a defect-ordered hexagonal pore structure antioxidant MXene aqueous potassium ion symmetric supercapacitor.

[0023] The beneficial effects of the present invention are:

[0024] (1) Through molten salt coating etching in a high-temperature air atmosphere, the process parameters are precisely controlled to ensure that the multi-layer hexagonal pore structure of the MXene material is retained, providing a high-speed channel for ion transport, while significantly improving the energy density of the material, enabling it to exhibit excellent performance in energy storage applications.

[0025] (2) The present invention directly prepares MAX phase Ti by sintering at 1600°C and then rapidly cooling it for a short time. 3 AlC 2 The precursor has regular hexagonal holes and loose interlayers, which makes subsequent etching easier, shortens the subsequent solid-phase etching time, and prevents the MXene material from being oxidized by long-term high-temperature sintering with a small amount of air that is not completely isolated, thus affecting the electrochemical properties of the material.

[0026] (3) Etching hexagonal pore MAX phase Ti by high temperature molten salt coating method in air atmosphere 3 AlC 2 Precursor, a multilayer hexagonal pore MXene material with a micro-oxidation protective layer was prepared. The surface of the MXene material forms a Cl end group instead of the hydrophilic end group etched by liquid phase acid, which weakens the aggressiveness of oxygen molecules and water molecules; at the same time, the unsaturated coordination bonds formed by the defective structure repel oxygen atoms; and under the joint action of trace amounts of metal oxides on the surface, a barrier is effectively constructed to resist the attack of oxygen molecules and water molecules, significantly improving the antioxidant properties of the MXene material; the enhancement of antioxidant properties effectively avoids the sharp decrease in specific surface area and specific capacity attenuation caused by oxidation of the MXene material. At the same time, this improvement also improves the rate performance and cycle stability of the material, allowing the MXene material to operate stably for a long time in the water-based symmetric supercapacitor energy storage device. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is the MAX phase Ti with hexagonal holes under rapid cooling of the present invention (corresponding to Example 1) 3 AlC 2 XRD patterns of precursor and multi-layer defect-ordered hexagonal pore structure antioxidant MXene materials;

[0028] Figure 2 It is the MAX phase Ti of the hexagonal holes of the present invention (corresponding to Example 1) 3 AlC 2 SEM images of materials;

[0029] Figure 3 This is a SEM image of the oxidation-resistant MXene material with multi-layer defect-ordered hexagonal pore structure of the present invention (corresponding to Example 1);

[0030] Figure 4This is a CV comparison diagram of the first cycle and the 25,000 cycle of the multi-layer defect ordered hexagonal pore structure antioxidant MXene aqueous potassium ion symmetric supercapacitor after 25,000 cycles of charge and discharge;

[0031] Figure 5 This is a SEM image of a conventional MAX without hexagonal holes that is not rapidly cooled by liquid nitrogen according to the present invention (corresponding to Example 1);

[0032] Figure 6 This is a CV comparison diagram of the first cycle and the 25,000 cycle of the conventional MXene aqueous potassium ion symmetric supercapacitor without hexagonal pores that is not rapidly cooled by liquid nitrogen according to the present invention (corresponding to Example 1) after 25,000 cycles of charge and discharge;

[0033] Figure 7 This is a SEM image of a multilayer MXene prepared by etching conventional MAX (without hexagonal holes) by a molten salt coating method under a high temperature vacuum atmosphere according to the present invention (corresponding to Example 2);

[0034] Figure 8 This is a CV comparison chart of the first cycle and 25,000 cycles of the aqueous potassium ion supercapacitor of the present invention (corresponding to Example 2) after 25,000 cycles of charge and discharge after the multilayer MXene prepared by etching conventional MAX by molten salt coating method in a vacuum atmosphere;

[0035] Fig. 9 This is a CV comparison chart of the first cycle and 25,000 cycles of the aqueous potassium ion symmetric supercapacitor obtained by etching hexagonal pore MAX in a vacuum atmosphere after 25,000 cycles of charge and discharge of the present invention (corresponding to Example 3);

[0036] Fig.10 This is a CV comparison chart of the first cycle and 25,000 cycles of the aqueous potassium ion symmetric supercapacitor after 25,000 cycles of charge and discharge of the multilayer hexagonal hole MXene obtained by etching the hexagonal carbon vacancy MAX for a long time according to the present invention (corresponding to Example 4);

[0037] Fig.11 This is a CV comparison chart of the first cycle and 25,000 cycles of the aqueous potassium ion symmetric supercapacitor after 25,000 cycles of charge and discharge of the multilayer hexagonal pore MXene obtained by microwave-assisted etching of the hexagonal pore MAX of the present invention (corresponding to Example 5). DETAILED DESCRIPTION

[0038] Example 1

[0039] The first step is defect ordering of MAX phase Ti with hexagonal holes 3 AlC 2 Preparation

[0040] Dehydrogenated titanium powder, pure aluminum powder and modified spherical graphite powder were placed in a vacuum hot pressing sintering furnace at a molar ratio of 2.95:1.05:1.6, and the furnace temperature was 1600°C; the vacuum hot pressing sintering furnace used had a power of 50KW, the pressure of the pressure head was set to 20T, and the diameter of the effective contact surface of the pressure head was Φ90mm; argon was used as the protective atmosphere in the furnace, and the inflation pressure was set to 0.03MPa; the temperature was raised to 1600°C according to the set heating scheme for hot pressing sintering for 3h, and after the hot pressing sintering was completed, it was transported to a liquid nitrogen device for rapid cooling for 0.5h to obtain the hexagonal pore MAX phase Ti 3 AlC 2 Materials; after rapid cooling with liquid nitrogen, the defect order is improved, and hexagonal exfoliated MAX phase Ti appears at the surface position where the order is improved 3 AlC 2 , falling off to form hexagonal holes; a hexagonal falling MAX phase Ti appears inside the structure with improved order 3 AlC 2 , the internal hexagonal exfoliated MAX phase Ti 3 AlC 2 The tightly layered MAX phase Ti will be pried apart 3 AlC 2 , so that the tight interlayer structure is transformed into a loose layer structure, providing a favorable foundation for subsequent etching.

[0041] The second step is to prepare the oxidation-resistant multilayer hexagonal pore MXene electrode material by molten salt coating in air atmosphere

[0042] The prepared MAX phase Ti with hexagonal holes 3 AlC 2 Materials and CuCl 2 and NaCl in a molar ratio of 1:3:6, and manually grind in an agate mortar for 30 minutes; a layer of NaCl salt bed is laid on the bottom of the alumina corundum ark in advance, and then the ground mixed powder is placed on the NaCl salt bed, and then the NaCl salt bed is covered on the mixed powder again, and finally the alumina corundum ark containing the product is placed in a muffle furnace and sintered at a constant temperature of 820°C for 3 hours in an air atmosphere; since oxygen cannot be completely isolated, a small amount of Al 2 O 3 The sintered product was taken out, cooled naturally, and then added with deionized water to dissolve and wash, remove the molten salt, filter, and retain the solid phase; then, according to the CuCl 2 With FeCl 3 FeCl with a molar ratio of 3:4 was added at a concentration of 1 mol / L 3 The generated copper element is removed from the solution of strong oxidant, and after filtration and cleaning, filtration is performed to retain the solid phase; according to the HCl and FeCl3 The molar ratio of 1:1 was 1 mol / L HCl solution was added to remove metal impurities, and the solid phase was retained by filtration; finally, deionized water was added again for washing and the mixture was ultrasonicated in an ultrasonic device for 1 h to further remove impurity salts. Finally, after filtration, vacuum drying and grinding, MXene (DH-Ti) with layered hexagonal pore defects was obtained. 3 C 2 ). The MAX phase Ti of the hexagonal pores after rapid cooling in Example 1 of the present invention 3 AlC 2 The X-ray diffraction patterns (XRD) of the multi-layer defect-ordered hexagonal pore structure antioxidant MXene materials are as follows: Figure 1 As shown; the scanning electron microscope image (SEM) of the hexagonal hole MAX is as follows Figure 2 (a) and Figure 2 (b) as shown; Figure 2 (a) and Figure 2 (b) It can be seen from the microscopic morphology that the holes are regular hexagonal in shape; combined with Figure 1 and Figure 2 It can be seen that the material prepared after rapid cooling is MAX phase Ti with hexagonal holes. 3 AlC 2 Material. Figure 3 This is the SEM image of the multi-layer defect-ordered hexagonal pore structure antioxidant MXene material prepared by the molten salt coating method in a high-temperature air atmosphere; Figure 3 It can be seen that the oxidation-resistant MXene material with a layered hexagonal pore structure prepared by etching at high temperature has the characteristics of uniform stratification and roughness; the surface roughness is caused by unsaturated coordination bonds and surface micro-oxidation; this improves the oxidation resistance of the multilayer hexagonal pore MXene; this lays a structural foundation for the multilayer hexagonal pore MXene aqueous potassium ion symmetric supercapacitor to have high long-cycle stability and high energy density.

[0043] Step 3: Assemble aqueous potassium ion symmetric supercapacitor

[0044] Defective multilayer hexagonal pore MXene materials are prepared as electrode materials and assembled into neutral water system potassium ion symmetric supercapacitors;

[0045] (1) Preparation of defective multilayer hexagonal pore MXene electrodes

[0046] The defective MXene (DH-Ti 3 C 2) was mixed with acetylene black and PVDF in a mass ratio of 8:1:1 and ground into a small amount, NMP was dropped into the slurry, coated on a cut 40 mm × 30 mm aluminum foil current collector, and rolled flat; placed in a vacuum drying oven and dried at 60 ° C for 24 hours, and after being taken out, a press was used to maintain a pressure of 20 MPa for 30 seconds to obtain a defect-ordered hexagonal pore structure antioxidant MXene material electrode sheet;

[0047] (2) Assembly of aqueous potassium ion symmetric supercapacitors

[0048] The defect-ordered hexagonal pore structure antioxidant MXene material electrode sheets are cut as positive and negative electrodes, and the negative electrode, separator, and positive electrode are stacked, packaged, and injected in sequence to obtain a defect-ordered hexagonal pore structure antioxidant MXene aqueous potassium ion symmetric supercapacitor.

[0049] The CV comparison diagram of the first cycle and the 25,000 cycles of the multi-layer defect-ordered hexagonal pore structure anti-oxidation MXene aqueous potassium ion supercapacitor after 25,000 cycles of charge and discharge is shown in the figure below. Figure 4 shown by Figure 4 It can be seen that the mass specific capacity of the multi-layer defect-ordered hexagonal pore structure anti-oxidation MXene aqueous potassium ion supercapacitor is as high as 335.6Fg -1 Even after 25,000 cycles of charge and discharge testing, the mass specific capacity is still 324.8Fg -1 ; The long-cycle charging mass specific capacity retention rate of defective multilayer hexagonal pore MXene aqueous potassium ion symmetric supercapacitors is as high as 96.8%; This provides a new strategy to solve the problem that in conventional aqueous potassium ion symmetric supercapacitors, the electrode materials are easily oxidized in water during long cycles, resulting in structural destruction, and then the specific surface area decreases and the rate performance decays, leading to a sharp decay in stability under long-term cycles.

[0050] Comparative Example 1

[0051] The first step is conventional MAX phase Ti 3 AlC 2 Preparation (after hot pressing and sintering, without liquid nitrogen rapid cooling, synthesize conventional MAX phase Ti without hexagonal holes 3 AlC 2 Precursor;)

[0052] Dehydrogenated titanium powder, pure aluminum powder and modified spherical graphite powder were placed in a vacuum hot pressing sintering furnace at a molar ratio of 2.95:1.05:1.6, and the furnace temperature was 1600°C; the vacuum hot pressing sintering furnace used had a power of 50KW, the pressure of the pressure head was set to 20T, and the diameter of the effective contact surface of the pressure head was Φ90mm; argon was used as the protective atmosphere in the furnace, and the inflation pressure was set to 0.03MPa; the temperature was raised to 1600°C according to the set heating scheme for hot pressing sintering for 4h; the sintered product was taken out and naturally cooled with the furnace to obtain MAX phase Ti 3 AlC 2 Material: Conventional Ti 3 AlC 2 There are no large number of ordered defects inside, and no hexagonal holes appear;

[0053] The second step is to prepare multilayer MXene (without hexagonal holes) electrode material by etching conventional MAX by molten salt coating method under high temperature air atmosphere.

[0054] The prepared MAX phase Ti without hexagonal holes 3 AlC 2 Materials and CuCl 2 and NaCl in a molar ratio of 1:3:6, and grind manually in an agate mortar for 30 minutes. A layer of NaCl salt bed is laid on the bottom of the alumina corundum ark in advance to provide a molten pool environment and isolate a certain amount of air. Then put the ground mixed powder into the NaCl salt bed, and then cover the mixed powder with a layer of NaCl salt bed. Finally, put the alumina corundum ark containing the product into a muffle furnace; sinter at a constant temperature of 820℃ for 3h in an air atmosphere; take out the sintered product, cool it naturally, add deionized water to dissolve and wash, filter, and retain the solid phase; then follow the CuCl 2 With FeCl 3 FeCl with a molar ratio of 3:4 was added at a concentration of 1 mol / L 3 The copper element is removed from the solution by strong oxidant, filtered and cleaned, and then filtered to retain the solid phase, and then HCl and FeCl 3 The molar ratio of 1:1 was 1 mol / L HCl solution was added to remove metal impurities, and the solid phase was retained by filtration; finally, deionized water was added again for washing and the mixture was ultrasonicated for 1 h to further remove impurity salts; finally, after filtration, vacuum drying and grinding, MXene (D-Ti 3 C 2 ).

[0055] Comparative Example 1: The scanning electron microscope image (SEM) of the conventional MAX without ordered defect structure and hexagonal holes without liquid nitrogen rapid cooling is as follows: Figure 5 shown; from Figure 5 The microscopic morphology shows that MAX is a compact structure, but the exposed surface area is smaller than that of the MAX material with hexagonal holes in Example 1. Therefore, the specific surface area of ​​the corresponding etched MXene is also smaller, and the energy density of the prepared symmetric supercapacitor is also smaller, but the oxidation resistance is improved and the long cycle stability is improved;

[0056] Step 3: Assemble aqueous potassium ion symmetric supercapacitor

[0057] Using multilayer MXene (without hexagonal pores) as electrode material, a neutral water system potassium ion symmetric supercapacitor was assembled;

[0058] (1) Preparation of multilayer MXene (without hexagonal pores) electrode materials

[0059] After the multilayer hexagonal pore MXene was mixed with acetylene black and PVDF in a mass ratio of 8:1:1 and ground for 1 hour, NMP was dropped into the mixture; the prepared negative electrode mixture was coated on a cut 40mm×30mm aluminum foil current collector and rolled flat; the electrode sheet was placed in a vacuum drying oven and dried at 60°C for 24 hours, and after being taken out, a press was used to maintain the pressure at 20MPa for 30s;

[0060] (2) Assembly of aqueous potassium ion symmetric supercapacitors

[0061] The cut hexagonal pore-free MXene electrode sheets are used as positive and negative electrodes, and the negative electrode, the separator, and the positive electrode are stacked, packaged, and injected in sequence to obtain a hexagonal pore-free MXene aqueous potassium ion symmetric supercapacitor;

[0062] Comparative Example 1 is a parallel test of Example 1 after rapid cooling with liquid nitrogen. Comparative Example 1 The CV comparison of the first cycle and the 25,000 cycles of the conventional MXene without hexagonal holes constructed by defect-free ordering without rapid cooling with liquid nitrogen is shown in the following figure. Figure 6 shown by Figure 6 It can be seen that relative to Example 1, the mass specific capacity of the MXene aqueous potassium ion supercapacitor without hexagonal holes in this comparative example is 286.5Fg -1 ; After 25,000 cycles of charge and discharge testing, the mass specific capacity is 254.7Fg -1 ; The long-cycle charging mass specific capacity retention rate of a conventional MXene aqueous potassium ion symmetric supercapacitor without hexagonal pores and defect-free ordering without liquid nitrogen rapid cooling is only 88.9%.

[0063] Comparative Example 2

[0064] The first step is conventional MAX phase Ti 3AlC 2 Preparation (after hot pressing and sintering, without liquid nitrogen rapid cooling, synthesize conventional MAX phase Ti without hexagonal holes 3 AlC 2 Precursor;)

[0065] Dehydrogenated titanium powder, pure aluminum powder and modified spherical graphite powder were placed in a vacuum hot pressing sintering furnace at a molar ratio of 2.95:1.05:1.6, and the furnace temperature was 1600°C; the vacuum hot pressing sintering furnace used had a power of 50KW, the pressure of the pressure head was set to 20T, and the diameter of the effective contact surface of the pressure head was Φ90mm; argon was used as the protective atmosphere in the furnace, and the inflation pressure was set to 0.03MPa; the temperature was raised to 1600°C according to the set heating scheme for hot pressing sintering for 4h; the sintered product was taken out and naturally cooled with the furnace to obtain MAX phase Ti 3 AlC 2 Material: Conventional Ti 3 AlC 2 There are no large number of ordered defects inside, and no hexagonal holes appear;

[0066] The second step is to use the molten salt coating method under high temperature vacuum atmosphere to etch conventional MAX to prepare multilayer MXene (without hexagonal holes) electrode material (vacuum atmosphere etching)

[0067] The prepared MAX phase Ti without hexagonal holes 3 AlC 2 Materials and CuCl 2 and NaCl in a molar ratio of 1:3:6, and manually grind in an agate mortar for 30 minutes; a layer of NaCl salt bed is laid on the bottom of the alumina corundum boat in advance to provide a molten pool environment; then the ground mixed powder is placed on the NaCl salt bed, and then a layer of NaCl salt bed is covered on the mixed powder; finally, the alumina corundum boat containing the product is placed in a vacuum muffle furnace; argon is introduced as a protective gas, and constant temperature sintering is performed at 820℃ for 8h; the sintered product is taken out, naturally cooled, deionized water is added to dissolve and wash, and filtered to retain the solid phase; then CuCl 2 With FeCl 3 FeCl with a molar ratio of 3:4 was added at a concentration of 1 mol / L 3 The solution is oxidized by strong oxidants to remove the generated copper; after filtration and cleaning, filtration is completed, the solid phase is retained, and HCl and FeCl are added. 3 The molar ratio of 1:1 was 1 mol / L HCl solution was added to remove metal impurities, and the solid phase was retained by filtration; finally, deionized water was added again for washing and the mixture was ultrasonicated for 1 h to further remove impurity salts; finally, after filtration, vacuum drying and grinding, MXene (TiO2) without hexagonal holes under vacuum was obtained.3 C 2 );

[0068] Comparative Example 2: A scanning electron microscope image (SEM) of a conventional MXene obtained by etching a conventional MAX without ordered defects and hexagonal holes without rapid cooling with liquid nitrogen in a vacuum atmosphere is shown in FIG. Figure 7 shown; from Figure 7 The microscopic morphology shows that MXene is a bulk layered structure with a smooth surface, but the exposed surface area is smaller than that of the MXene material with hexagonal holes in Example 1. Therefore, the energy density of the prepared symmetric supercapacitor is small, and the surface is not slightly oxidized when etched in a vacuum atmosphere, resulting in poor long-cycle stability.

[0069] Step 3: Assemble aqueous potassium ion symmetric supercapacitor

[0070] Using multilayer MXene (without hexagonal pores) under vacuum as electrode material, a neutral water system potassium ion symmetric supercapacitor was assembled;

[0071] (1) Preparation of multilayer MXene (without hexagonal pores) electrode materials under vacuum

[0072] After the multilayer MXene was mixed and ground with acetylene black and PVDF in a mass ratio of 8:1:1 under vacuum for 1 hour, NMP was dropped into the mixture to form a mixture; the prepared negative electrode mixture was coated on a cut 40mm×30mm aluminum foil current collector and rolled flat; the electrode sheet was placed in a vacuum drying oven and dried at 60°C for 24 hours, and after being taken out, a press was used to maintain the pressure at 20MPa for 30s;

[0073] (2) Assembly of aqueous potassium ion symmetric supercapacitors

[0074] The cut MXene electrode sheet without hexagonal holes under vacuum is used as the positive electrode and the negative electrode, and the negative electrode, the diaphragm, and the positive electrode are stacked, packaged, and injected in order to obtain a MXene aqueous potassium ion symmetric supercapacitor without hexagonal holes under vacuum; Comparative Example 2 is a parallel test of Example 1 by etching in a vacuum atmosphere without rapid cooling with liquid nitrogen. The conventional MXene aqueous potassium ion symmetric supercapacitor obtained by etching in a vacuum atmosphere without rapid cooling with liquid nitrogen without ordered defects and without hexagonal holes is shown in the CV comparison diagram of the first cycle and the 25,000 cycles after 25,000 cycles of charge and discharge. Figure 8 shown by Figure 8 It can be seen that relative to Example 1, the mass specific capacity of the MXene aqueous potassium ion symmetric supercapacitor without hexagonal holes under vacuum in this comparative example is 230.5Fg -1 ; After 25,000 cycles of charge and discharge testing, the mass specific capacity is 167.4Fg-1 ; In this comparative example, the long-cycle charging mass specific capacity retention rate of the conventional MXene aqueous potassium ion symmetric supercapacitor obtained by etching the conventional MAX without hexagonal pores without ordered defects in a vacuum atmosphere without rapid cooling with liquid nitrogen is only 72.6%.

[0075] Comparative Example 3

[0076] The first step is to use the molten salt coating method under high temperature vacuum atmosphere to etch the hexagonal pore MAX to prepare multi-layer hexagonal pore MXene electrode material (vacuum atmosphere etching)

[0077] The MAX phase Ti with hexagonal holes prepared in Example 1 3 AlC 2 Materials and CuCl 2 and NaCl in a molar ratio of 1:3:6, and manually grind in an agate mortar for 30 minutes; a layer of NaCl salt bed is laid on the bottom of the alumina corundum boat in advance to provide a molten pool environment; then the ground mixed powder is placed on the NaCl salt bed, and then a layer of NaCl salt bed is covered on the mixed powder; finally, the alumina corundum boat containing the product is placed in a vacuum muffle furnace; argon is introduced as a protective gas, and constant temperature sintering is performed at 820℃ for 3h; the sintered product is taken out, naturally cooled, deionized water is added to dissolve and wash, and filtered to retain the solid phase; then CuCl 2 With FeCl 3 FeCl with a molar ratio of 3:4 was added at a concentration of 1 mol / L 3 The solution is oxidized by strong oxidants to remove the generated copper; after filtration and cleaning, filtration is completed, the solid phase is retained, and HCl and FeCl are added. 3 The molar ratio of 1:1 was 1 mol / L HCl solution was added to remove metal impurities, and the solid phase was retained by filtration; finally, deionized water was added again for washing and the mixture was ultrasonicated for 1 h to further remove impurity salts; finally, after filtration, vacuum drying and grinding, multilayer hexagonal pore MXene (H-Ti 3 C 2 );

[0078] Step 2: Assemble aqueous potassium ion symmetric supercapacitor

[0079] Using multilayer hexagonal pore MXene electrode materials under vacuum as electrode materials, a neutral water system potassium ion symmetric supercapacitor is assembled;

[0080] (1) Preparation of multilayer hexagonal pore MXene electrode materials under vacuum

[0081] After the multilayer hexagonal pore MXene was mixed with acetylene black and PVDF in a mass ratio of 8:1:1 under vacuum and ground for 1 hour, NMP was dropped into the mixture; the prepared negative electrode mixture was coated on a cut 40mm×30mm aluminum foil current collector and rolled flat; the electrode sheet was placed in a vacuum drying oven and dried at 60°C for 24 hours, and after being taken out, a press was used to maintain the pressure at 20MPa for 30s;

[0082] (2) Assembly of aqueous potassium ion symmetric supercapacitors

[0083] The cut multi-layer hexagonal pore MXene electrode sheets under vacuum are used as positive and negative electrodes, and the negative electrode, separator, and positive electrode are stacked, packaged, and injected in sequence to obtain a multi-layer hexagonal pore MXene aqueous potassium ion symmetric supercapacitor under vacuum; the CV comparison diagram of the first cycle and 25,000 cycles of the multi-layer hexagonal pore MXene aqueous potassium ion symmetric supercapacitor obtained by etching the hexagonal pore MAX under vacuum atmosphere in this comparative example is as follows: Fig. 9 shown by Fig. 9 It can be seen that, relative to Example 1, the mass specific capacity of the multilayer hexagonal pore MXene water-based potassium ion symmetric supercapacitor under vacuum in this comparative example is 270.3Fg-1; after 25,000 cycles of long-cycle charge and discharge test, the mass specific capacity is 186.2Fg-1; the long-cycle charging mass specific capacity retention rate of the water-based potassium ion symmetric supercapacitor obtained by etching the hexagonal pore MAX in vacuum atmosphere in this comparative example is only 68.9%. The multilayer hexagonal pore MXene obtained by etching the hexagonal pore MAX in vacuum atmosphere in Comparative Example 3 has a higher specific capacity than Comparative Example 2, but its antioxidant performance after long-cycle testing is significantly reduced compared with Example 1.

[0084] Comparative Example 4

[0085] The first step is defect ordering of MAX phase Ti with hexagonal carbon vacancies 3 AlC 2 Preparation

[0086] Dehydrogenated titanium powder, pure aluminum powder and modified spherical graphite powder were placed in a vacuum hot pressing sintering furnace at a molar ratio of 2.95:1.05:1.6, and the furnace temperature was 1400°C; the vacuum hot pressing sintering furnace used had a power of 50KW, the pressure of the pressure head was set to 10T, and the diameter of the effective contact surface of the pressure head was Φ85mm; argon was used as the protective atmosphere in the furnace, and the inflation pressure was set to 0.03MPa; the temperature was raised to 1400°C according to the set heating scheme for hot pressing sintering for 3h; after the hot pressing sintering was completed, it was transported to a liquid nitrogen device for rapid cooling for 2h to obtain the hexagonal carbon vacancy MAX phase Ti3AlC2;

[0087] The second step is to use the molten salt coating method in a long-term high-temperature air atmosphere to etch MAX with hexagonal carbon vacancies to prepare multi-layer hexagonal pore MXene electrode materials (long-term etching)

[0088] The prepared MAX phase Ti with hexagonal carbon vacancies 3 AlC 2 With CuCl 2 and NaCl in a molar ratio of 1:3:6, and manually grind in an agate mortar for 30 minutes; a layer of NaCl salt bed is laid on the bottom of the alumina corundum ark in advance to provide a molten pool environment; then the ground mixed powder is placed on the NaCl salt bed, and then a layer of NaCl salt bed is covered on the mixed powder; finally, the alumina corundum ark containing the product is placed in a muffle furnace and sintered at a constant temperature of 820°C for 3 hours in an air atmosphere. No yellow smoke during solid phase etching appears, so the constant temperature etching is continued until yellow smoke appears for 8 hours and then the etching is stopped; the sintered product is taken out, naturally cooled, and deionized water is added to dissolve and wash, and the solid phase is retained by suction; then the CuCl 2 With FeCl 3 FeCl with a molar ratio of 3:4 was added at a concentration of 1 mol / L 3 The solution is oxidized by strong oxidants to remove the generated copper; after filtration and cleaning, filtration is completed, the solid phase is retained, and HCl and FeCl are added. 3 The molar ratio of 1:1 was 1mol / L HCl solution was added to remove metal impurities, and the solid phase was retained by filtration; finally, deionized water was added again for washing and the mixture was ultrasonicated for 1h to further remove impurity salts; finally, after filtration, vacuum drying and grinding, multilayer hexagonal pore MXene (LH-Ti 3 C 2 ).

[0089] Step 3: Assemble aqueous potassium ion symmetric supercapacitor

[0090] The MXene electrode material with multiple layers of hexagonal holes etched for a long time is used as the electrode material to assemble a neutral water system potassium ion symmetric supercapacitor;

[0091] (1) Preparation of multilayer hexagonal pore MXene electrode materials by long-term etching

[0092] After long-time etching of multi-layer hexagonal pore MXene, acetylene black and PVDF were mixed and ground at a mass ratio of 8:1:1 for 1 hour, NMP was dropped into the mixture to form a mixture; the prepared negative electrode mixture was coated on a cut 40mm×30mm aluminum foil current collector and rolled flat; the electrode sheet was placed in a vacuum drying oven and dried at 60°C for 24 hours, and after being taken out, a press was used to maintain the pressure at 20MPa for 30s;

[0093] (2) Assembly of aqueous potassium ion symmetric supercapacitors

[0094] The multi-layer hexagonal pore MXene electrode sheets etched for a long time after cutting are used as positive and negative electrodes, and the negative electrode, separator, and positive electrode are stacked, packaged, and injected in sequence to obtain a long-etched hexagonal pore MXene aqueous potassium ion symmetric supercapacitor; the CV comparison diagram of the first cycle and 25,000 cycles of the aqueous potassium ion symmetric supercapacitor of the multi-layer hexagonal pore MXene obtained by long-term etching of the hexagonal carbon vacancy MAX in this comparative example after 25,000 cycles of charge and discharge is shown in Fig.10 shown by Fig.10 It can be seen that, relative to Example 1, the mass specific capacity of the long-term etched multi-layer hexagonal pore MXene water-based potassium ion symmetric supercapacitor of this comparative example is 126.8Fg-1; after 25,000 cycles of long-cycle charge and discharge test, the mass specific capacity is 64.5Fg-1; the long-cycle charging mass specific capacity retention rate of the water-based potassium ion symmetric supercapacitor obtained by long-term etching of the multi-layer hexagonal pore MXene with hexagonal carbon vacancies MAX in this comparative example is only 50.9%. When the multi-layer hexagonal pore MXene obtained by etching the hexagonal carbon vacancy MAX for a long time in Comparative Example 4 was severely oxidized (the powder color turned white), resulting in its low specific capacity and poor cycle stability.

[0095] Comparative Example 5

[0096] The first step is defect ordering of MAX phase Ti with hexagonal holes 3 AlC 2 Preparation

[0097] Dehydrogenated titanium powder, pure aluminum powder and modified spherical graphite powder were placed in a vacuum hot pressing sintering furnace at a molar ratio of 2.95:1.05:1.6, and the furnace temperature was 1600°C; the vacuum hot pressing sintering furnace used had a power of 50KW, the pressure of the pressure head was set to 20T, and the diameter of the effective contact surface of the pressure head was Φ90mm; argon was used as the protective atmosphere in the furnace, and the inflation pressure was set to 0.03MPa; the temperature was raised to 1600°C according to the set heating scheme and hot pressing sintering was performed for 3h to obtain the MAX phase Ti with hexagonal pores. 3 AlC 2 After hot pressing and sintering, the product was transported to a liquid nitrogen device for rapid cooling for 0.5 h, and the defect order was improved. Hexagonal exfoliated MAX phase Ti appeared at the surface position with improved order. 3 AlC 2 , falling off to form hexagonal holes; a hexagonal falling MAX phase Ti appears inside the structure with improved order 3 AlC 2 , the internal hexagonal exfoliated MAX phase Ti 3 AlC2 The tightly layered MAX phase Ti will be pried apart 3 AlC 2 , so that the tight interlayer structure is transformed into a loose layer structure, providing a favorable foundation for subsequent etching.

[0098] The second step is to prepare multilayer hexagonal pore MXene electrode materials by microwave-assisted etching.

[0099] Weigh 2g of MAX phase Ti with hexagonal holes 3 AlC 2 Set aside, then draw 40mL of the mixed solution of ammonium fluoride and hydrochloric acid (the mass ratio of ammonium fluoride to hydrochloric acid is 1:7) into a polytetrafluoroethylene beaker, and slowly stir the hexagonal pore MAX phase Ti under magnetic stirring. 3 AlC 2 The mixture was added to a mixture of ammonium fluoride and hydrochloric acid; the mixture was placed in a microwave reactor for microwave-assisted etching for 2 hours, with a microwave power of 300 W, a frequency of 2.45 GHz, and a pressure of 1 Gpa; the reaction solution was then placed in an ultrasonic device for ultrasonic oscillation at room temperature for 2 hours; the mixed solution after ultrasonic oscillation was taken out and placed in a centrifuge for solid-liquid separation at a high speed of 3000 rpm; the precipitate after centrifugation was washed with deionized water until the pH value of the solution was equal to 6; the solution was filtered for solid-liquid separation; the filtered powder was placed in a vacuum drying oven for drying for 6 hours; and finally, the multilayer hexagonal pore MXene (WH-Ti) was obtained by grinding and collection. 3 C 2 ) Electrode materials;

[0100] Step 3: Assemble aqueous potassium ion supercapacitors

[0101] The multilayer hexagonal pore MXene material obtained by microwave-assisted etching was used as the electrode material to assemble a neutral water-based potassium ion symmetric supercapacitor.

[0102] (1) Preparation of multilayer hexagonal pore MXene electrode materials by microwave-assisted etching

[0103] The microwave-assisted etched multilayer hexagonal pore MXene was mixed with acetylene black and PVDF in a mass ratio of 8:1:1 and ground for 1 hour, and then NMP was dropped into the mixture to form a mixture; the prepared negative electrode mixture was coated on a cut 40mm×30mm aluminum foil current collector and rolled flat; the electrode sheet was placed in a vacuum drying oven and dried at 60°C for 24 hours, and after being taken out, a press was used to maintain the pressure at 20MPa for 30s;

[0104] (2) Assembly of aqueous potassium ion symmetric supercapacitors

[0105] The microwave-assisted etching multilayer hexagonal pore MXene electrode sheets after slicing are stacked, packaged, and injected in the order of negative electrode, diaphragm, and positive electrode to obtain a microwave-assisted etched hexagonal pore MXene aqueous potassium ion symmetric supercapacitor; the CV comparison diagram of the first cycle and 25,000 cycles of the multilayer hexagonal pore MXene aqueous potassium ion symmetric supercapacitor obtained by microwave-assisted etching of hexagonal pore MAX in this comparative example after 25,000 cycles of charge and discharge is shown in the figure Fig.11 shown by Fig.11 It can be seen that, relative to Example 1, the mass specific capacity of the microwave-assisted etched multilayer hexagonal pore MXene water-based potassium ion symmetric supercapacitor of this comparative example is 304.9Fg-1; after 25,000 cycles of long-cycle charge and discharge test, the mass specific capacity is 197.9Fg-1; the long-cycle charging mass specific capacity retention rate of the water-based potassium ion symmetric supercapacitor of the multilayer hexagonal pore MXene obtained by microwave-assisted etching of hexagonal pore MAX in this comparative example is only 64.9%. The multilayer hexagonal pore MXene obtained by microwave-assisted etching of hexagonal pore MAX in Comparative Example 5 has a higher specific capacity, but its antioxidant performance is insufficient, which is caused by the fact that the liquid phase etching does not cover the multilayer hexagonal pore MXene with a protective coat.

[0106] The above are only specific embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a defect-ordered hexagonal pore structure antioxidant MXene material, characterized by: The specific steps are as follows: (1) Preparation of hexagonal pore MAX phase Ti3AlC2 Dehydrogenated titanium powder, pure aluminum powder and modified spherical graphite powder were hot pressed and sintered for 4 hours in an argon atmosphere, wherein the sintering temperature was 1600°C and the head pressure of the vacuum hot pressing sintering furnace was set to 20T; after the hot pressing sintering was completed, liquid nitrogen was extremely rapidly cooled for 0.5 hours to obtain MAX phase Ti3AlC2 with hexagonal pores; (2) Preparation of multilayer hexagonal MXene by molten salt coating in high temperature air atmosphere The hexagonal pore MAX phase Ti3AlC2 is mixed with CuCl2 and NaCl in a molar ratio of 1:3:6 and ground for 30 minutes to obtain a hexagonal pore MAX phase Ti3AlC2-CuCl2-NaCl mixed powder; a NaCl salt bed is laid on the bottom of the alumina corundum boat, and then the hexagonal pore MAX phase Ti3AlC2-CuCl2-NaCl mixed powder is placed in the alumina corundum boat with the NaCl salt bed, and then a NaCl salt bed is covered on the hexagonal pore MAX phase Ti3AlC2-CuCl2-NaCl mixed powder. The boat was placed in a muffle furnace and sintered at a constant temperature of 820°C for 3 hours in an air atmosphere; the sintered product was naturally cooled to room temperature, deionized water was added to dissolve and wash, and the solid phase was retained; then, CuCl2 was added to FeCl3 solution at a molar ratio of 3:4, and the mixture was filtered and washed with clean water to retain the solid phase; HCl solution was added at a molar ratio of 1:1 to FeCl3 to remove impurities again, and the solid phase was retained by filtration; finally, deionized water was added to wash and the mixture was placed in an ultrasonic device for 1 hour, filtered, vacuum dried and ground to obtain a defect-ordered hexagonal pore structure antioxidant MXene material.

2. The method for preparing the defect-ordered hexagonal pore structure antioxidant MXene material according to claim 1, characterized in that: The molar ratio of the dehydrogenated titanium powder, the pure aluminum powder and the modified spherical graphite powder is 2.95:1.05:1.

6.

3. The method for preparing the defect-ordered hexagonal pore structure antioxidant MXene material according to claim 1, characterized in that: The concentration of the FeCl3 solution is 1 mol / L.

4. The method for preparing the defect-ordered hexagonal pore structure antioxidant MXene material according to claim 1, characterized in that: The concentration of the HCl solution is 1 mol / L.

5. The method for preparing the defective multilayer hexagonal hole MXene electrode material according to claim 1, characterized in that: During hot pressing sintering, the sintering power is 50KW.

6. The method for preparing the defect-ordered hexagonal pore structure antioxidant MXene material according to claim 1, characterized in that: The diameter of the effective contact surface of the pressure head of the vacuum hot pressing sintering furnace is Φ90mm.

7. The method for preparing the defect-ordered hexagonal pore structure antioxidant MXene material according to claim 1, characterized in that: The filling pressure of the argon protective atmosphere is 0.03MPa.

8. An application of the defect-ordered hexagonal pore structure antioxidant MXene material prepared by the preparation method as claimed in claim 1 in an aqueous potassium ion symmetric supercapacitor.

9. The use of the defect-ordered hexagonal pore structure antioxidant MXene material according to claim 8 in an aqueous potassium ion symmetric supercapacitor, characterized in that: The defect-ordered hexagonal pore structure antioxidant MXene material is used as an electrode material for an aqueous potassium ion symmetric supercapacitor; The preparation process of aqueous potassium ion supercapacitor is as follows: (1) Preparation of defective multilayer hexagonal pore MXene electrodes The defect-ordered hexagonal pore structure antioxidant MXene material was mixed with acetylene black and PVDF in a mass ratio of 8:1:1 and ground for 1 hour, NMP was added dropwise to form a slurry, coated on an aluminum foil current collector, and rolled flat, dried at 60°C for 24 hours, and maintained at a pressure of 20MPa for 30 seconds using a press to obtain a defect-ordered hexagonal pore structure antioxidant MXene material electrode; (2) Assembly of aqueous potassium ion symmetric supercapacitors The defect-ordered hexagonal pore structure antioxidant MXene material electrode as the negative electrode, the separator, and the defect-ordered hexagonal pore structure antioxidant MXene material electrode as the positive electrode are sequentially loaded into the capacitor shell, packaged, and injected with electrolyte to obtain a defect-ordered hexagonal pore structure antioxidant MXene aqueous potassium ion symmetric supercapacitor.

Citation Information

Patent Citations

  • Li2S-based battery positive electrode material based on MXene and transition metal nitrogen oxide composite structure, and synthesis method

    CN113690444A

  • MAX phase stratified material containing antimony element at A site and preparation method and application thereof

    CN113816378A

  • Preparation method of MXene quantum dot drug loading system

    CN114644338A

  • Method for preparing antioxidant MXene by using low-temperature molten salt system

    CN114956085A

  • Sandwich composite material, preparation method and application thereof, and preparation method of aqueous zinc ion battery negative electrode

    CN116417601A

Cited By

  • Method for preparing antioxidant MXene through electrochemical stripping

    CN120774420A